Uncommon cutaneous lymphoproliferative disorders in two patients with rheumatoid arthritis. (31st March 2016) - Carroll, Melissa; Biswas, Neela; Wheller, Laura; Shepherd, Victoria; Strutton, Geoffrey M
Abstract: Two patients with rheumatoid arthritis developed rare cutaneous lymphomas while on long‐term immunosuppression: extranodal NK/T‐cell lymphoma, nasal and plasmablastic lymphoma. We give an overview of these lymphomas in the context of rheumatoid arthritis and postulate whether these diagnoses could be iatrogenically induced.